“R U OK TEACHER?”: Online Space for Thai University Instructors’ Mental Health - SaeChia, Thongchai (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2022)
Online space is a space for people, who share the mutual interest, to exchangetheir ideas and contribute their community. There are many online spaces for university instructors, but “R U OK TEACHER?” is an online space that represent the various problems they faced with the wed administrator will continually puts various issues, and many university instructors will exchange their opinions more than these of other online spaces. This article aimed to study the representation of university instructors’ problems on this online space, which is a space to express their frustrations in their profession as appeared 108 posts on the online space from June 6th 2015 to January 29th 2019. The result the “R U OK TEACHER?” is an online space that represents the university instructors’ problems they faced by uses of satire for humor characteristics The most common problem represented in the online space is a problem about the burden workloads of Thai university instructors, followed by the sequences of problems with colleagues, problem about their student, and problem about the university policy. Techniques used in problem representation and comment exchanges that Facebook users who share their opinions make this online space be a space to promote Thai university instructors’ mental health.